Case Report: Digitally driven tooth autotransplantation using surgical templates and three-dimensional printed donor tooth replica - Babiuc, Iuliana; Diaconeasa, Marius Ștefan; Perieanu, Viorel Ștefan; Malița, Mădălina Adriana; Beuran, Irina Adriana; Burlibașa, Mihai (Frontiers in Oral Health, 2025)
Tooth autotransplantation is a procedure involving the surgical repositioning of a tooth or dental germ from one site in the mouth to another within the same individual. A successful procedure requires a donor tooth with healthy cementum and periodontium, gentle surgical maneuvers, a well-fitted neoalveolus, and a short extraalveolar time of the donor tooth. Digital technology increases the accuracy and predictability of the tooth autotransplantation procedure. Surgical templates generate a more precise neoalveolus, with good stability of the donor tooth, and decrease the surgical time. Using a donor tooth replica ensures an optimal morphology of the new alveolus, thus reducing the injury of the root and the extraoral time of the donor tooth. This case report presents the tooth autotransplantation technique, that was employed to reposition a maxillary premolar with two fused roots on a mandibular recipient site. Digital planning, two surgical guides (one for each root), and a 3D printed tooth replica were used to ensure good accuracy, prognosis, and reduced treatment time. The procedure is conservative and offers considerable advantages to the patient, such as retaining natural teeth and proprioception.